KADAR TESTOSTERON INTRATESTIKULAR TIKUS Rattus novergicus STRAIN Sprague dawley AKIBAT PEMBERIAN KURKUMIN SETELAH STIMULASI hCG - Khatimah, Husnul (Fakultas Kedokteran Universitas Lambung Mangkurat, 2015)
Curcumin is an active agent on Curcuma longa. Curcumin had so many biologic activities; one of them is anti fertility. Curcumin research in male reproductive system had been done. Curcumin reduced testis weight and serum testosterone. This study is done to know curcumin effect on testosterone intratesticular level in rats. This study was conducted to 15 male Sprague dawley rats aged 90 days. Rats divided into 5 groups treatment : group 1 rats were given aquades, group 2 rats were given a single dose of 50 IU hCG, group 3 rats were given CMC, group 4 rats were given curcumin, group 5 rats were given hCG and curcumin. Rats were sacrified on age 91 days. Testis was taken, homogenizer and sentrifuge. Supernatant was taken in order to measured intratesticular testosterone level. The result of this study show intratesticular testosterone level from 5 group treatment, each group are n = 3, are (1) 44.36±1.30 (aquades), (2) 41.53±16.44 (hCG), (3) 37.33±9.05 (CMC), (4) 54.16±29.82 (curcumin), (5) 49.36±5.05 (hCG + curcuminStatistic analytic with ANOVA showed there is no significant difference (p>0.05). This study had a conclusion that curcumin not decreased testosterone intratestikular level in rats. Keywords: curcumin, hCG, intratesticular testosterone